2010
DOI: 10.1007/s12517-010-0202-6
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characterization of groundwater from shallow aquifer surrounding Fetzara Lake N. E. Algeria

Abstract: Hydrogeochemical investigations were carried out around Fetzara Lake, Northeast Algeria, to assess the quality of groundwater for its suitability for drinking and irrigation purposes. The groundwater chemistry is mainly controlled by the water-rock interactions, but also influenced by other processes such as evapotranspiration and ion exchange. Groundwater samples collected, during two periods (1993 and 2007) from wells in the area were analyzed for pH, EC, TDS, Ca 2+ , Mg 2+ , Na + , K + , CO 3 2− , HCO 3 − ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…La température moyenne est de 11C° en hiver et de 25 C° en été. Bien que la température estivale peut atteindre 40 ° C (Rouabhia & al. 2012).…”
Section: Zone D'étudeunclassified
“…La température moyenne est de 11C° en hiver et de 25 C° en été. Bien que la température estivale peut atteindre 40 ° C (Rouabhia & al. 2012).…”
Section: Zone D'étudeunclassified
“…[54]. So, the quality of groundwater is subjected to the interaction between geological and hydrological processes [1,11,12,25,33,51,60,88,93,102].…”
Section: Introductionmentioning
confidence: 99%
“…This research shows that the quality of groundwater and the geochemistry of the area depends on its geology. Some researchers conducted a review of Fetzara Lake Water Hydrochemistry to assess groundwater quality for drinking or farming [9]. They found that groundwater chemistry is more dependent on the interaction of water and bedrock, but is often also affected by other factors, such as steam and ion exchange.…”
Section: Introductionmentioning
confidence: 99%